Creative Graphic Thinking and Contemporary Graphic Representation - Barban Franceschi, Roberta (Advances in desing, music and arts, EIMAD 2020, 2022)
The article fundamentally seeks to demonstrate to what extent technologies have changed the graphic thinking process of industrial designers. It verifies what type of innovation graphic representation has undergone in the ideation and creation phase, and detects that creative graphic thinking is the result of the three thoughts: creative thinking, where "associations" are the essence of our imaginative world, created between mind and knowledge through combinations and associations; project thinking, a dialogue between the solution and the discovery of problems, a fractal process in constant transformation, the designer's faculty in which he expresses, formulates and materializes his ideas; and graphic thinking, which is manifested in the conceptual design stages, to the development of ideas, the language of communication in a design project, dialogue and the expression of the designer's thought. The research recognizes a new perception, a new way of doing and thinking both graphically, creatively and at project level, amplifying the possibilities of graphic registers identified as five types of creative graphic thinking: analogue, three-dimensional analogue, digital, three-dimensional digital and experimental digital-diagram. The contemporary design process changes the act of creative drawing carried out in two dimensions towards a virtual modeling in three dimensions, creating surfaces freely. A process with greater experimental freedom.
Keywords: creative graphic thinking; contemporary graphic representation; ideation; WOS(2); Scopus(2)